Review of the book The Rights of the Oppressed - CERQUEIRA NETO, Sebastião Pinheiro Gonçalves de (Geografares, 2024)
My work as a geographer has always led me to understand the dynamics of the poor and at the same time the causes of their marginalization in various territories. I always learned in school, in the early cycles, that society would be largely to blame for the situation of abyss between the poor and the rich, especially the middle class. The attribution of an alleged “culpability” of society in relation to the creation of a bipolar scenario between “opaque places and luminous places”, an expression coined by Milton Santos, seems to have left the State aside and very comfortable. The book “The Rights of the Oppressed” is a criticism of the absence of States with regard to the lack of justice in poor territories. Boaventura de Sousa Santos shows us how the societies of countries find solutions to their internal conflicts such as Cape Verde, Angola, Bolivia, Colombia, Ecuador, Macau and Mozambique; and in the Jacarezinho favela in Rio de Janeiro, which is the core of this review.